Development and Validation of the Primary Care Team Dynamics Survey. (25th November 2014) - Song, Hummy; Chien, Alyna T.; Fisher, Josephine; Martin, Julia; Peters, Antoinette S.; Hacker, Karen; Rosenthal, Meredith B.; Singer, Sara J.
<x xml:space="preserve">Abstract</x> Objective To develop and validate a survey instrument designed to measure team dynamics in primary care. Data Sources/Study Setting We studied 1, 080 physician and nonphysician health care professionals working at 18 primary care practices participating in a learning collaborative aimed at improving team‐based care. Study Design We developed a conceptual model and administered a cross‐sectional survey addressing team dynamics, and we assessed reliability and discriminant validity of survey factors and the overall survey's goodness‐of‐fit using structural equation modeling. Data Collection We administered the survey between September 2012 and March 2013. Principal Findings Overall response rate was 68 percent (732 respondents). Results support a seven‐factor model of team dynamics, suggesting that conditions for team effectiveness, shared understanding, and three supportive processes are associated with acting and feeling like a team and, in turn, perceived team effectiveness. This model demonstrated adequate fit (goodness‐of‐fit index: 0.91), scale reliability (Cronbach's alphas: 0.71–0.91), and discriminant validity (average factor correlations: 0.49). Conclusions It is possible to measure primary care team dynamics reliably using a 29‐item survey. This survey may be used in ambulatory settings to study teamwork and explore the effect of efforts to improve team‐based care. Future studies should demonstrate the importance of team dynamics for markers of team effectiveness (e.g., work satisfaction, care quality, clinical outcomes).